2023
DOI: 10.1021/acs.est.3c00581
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Transporter as a Potential Carrier Protein for the Root-to-Shoot Translocation of Polybrominated Diphenyl Ethers in Rice

Abstract: As typical persistent organic pollutants, polybrominated diphenyl ethers (PBDEs) tend to accumulate in edible parts of rice, posing great ecological and health risks. The translocation of PBDEs from underground to aboveground parts of rice is a crucial procedure to determine the final bioaccumulation level. Herein, this study aimed to identify the transporter proteins for PBDEs in rice plants in order to strengthen our understanding of the bioaccumulation mechanism and the potential prevention strategy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…As shown in Figure a, compared to roots (δ 13 C: −33.1 to −32.6‰), the δ 13 C values of BDE-47 in the shoots were overall higher during the whole period of incubation, with the ranges of −30.2 to −29.4‰ by considering measurement uncertainty of 0.5‰, indicating the enrichment in heavier isotopes during the translocation from roots to shoots. This phenomenon was also observed for translocation of hexachlorocyclohexane in the hydroponic and soil-wheat systems. , Due to the hindrance of endodermic Casparian strip, the compounds have to cross at least one lipid bilayer to enter the vascular bundle prior to the acropetal translocation from roots, and the transmembrane transport was depended on the channels and transporters of cell membrane. , Recently, Chen et al found that lysine histidine transporter protein acted as a cellular carrier for the root-to-shoot translocation of PBDEs in rice . In the present study, an energy-dependent active process was discovered by the inhibitors during the uptake of BDE-47 by wheat roots in addition to energy-free diffusion mediated by aquaporins and anion channels.…”
Section: Resultssupporting
confidence: 75%
“…As shown in Figure a, compared to roots (δ 13 C: −33.1 to −32.6‰), the δ 13 C values of BDE-47 in the shoots were overall higher during the whole period of incubation, with the ranges of −30.2 to −29.4‰ by considering measurement uncertainty of 0.5‰, indicating the enrichment in heavier isotopes during the translocation from roots to shoots. This phenomenon was also observed for translocation of hexachlorocyclohexane in the hydroponic and soil-wheat systems. , Due to the hindrance of endodermic Casparian strip, the compounds have to cross at least one lipid bilayer to enter the vascular bundle prior to the acropetal translocation from roots, and the transmembrane transport was depended on the channels and transporters of cell membrane. , Recently, Chen et al found that lysine histidine transporter protein acted as a cellular carrier for the root-to-shoot translocation of PBDEs in rice . In the present study, an energy-dependent active process was discovered by the inhibitors during the uptake of BDE-47 by wheat roots in addition to energy-free diffusion mediated by aquaporins and anion channels.…”
Section: Resultssupporting
confidence: 75%
“…Molecular docking, a computational technique based on principles of spatial arrangement and energy complementarity, is commonly utilized to forecast the affinity between chemical entities (ligands) and biomolecules (receptors), , thereby playing a key role in unraveling the toxicity mechanisms posed by environmental contaminants. In this study, the interaction between three generations of antibiotics and the psbD protein was performed via a comparative molecular docking simulation.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro competition binding experiments were first performed based on the equilibrium dialysis, which has been widely applied to evaluate the binding affinities of drug compounds with proteins. , The sorption of BUVSs and ATP to the dialysis bags was negligible (0.12–1.27%) (Figure S6). However, BUVSs and ATP were found to be significantly sorbed to CDPK in the individual sorption experiments (Figure S7), with the saturated sorption fractions (mean value) of 26.2–28.3 and 26.8%, respectively, when the initial concentration of chemicals was 75 μM and the incubation duration was 24 h (Figure S8).…”
Section: Resultsmentioning
confidence: 99%